4-Hydroxybenzaldehyde accelerates acute wound healing through activation of focal adhesion signalling in keratinocytes. Issue 1 (December 2017) - Kang, Chan; Han, Ye; Kim, Jean; Oh, Joo; Cho, Yoon; Lee, Eun
Abstract 4-Hydroxybenzaldehyde (4-HBA) is a naturally occurring benzaldehyde and the major active constituent ofGastrodia elata . While recent studies have demonstrated metabolic effects of 4-HBA, little is known about the physiological role of 4-HBA in acute wound healing. Here, we investigated the effects and mechanisms of 4-HBA on acute wound healing. Using anin vitro approach, we found that 4-HBA significantly promoted keratinocyte cell migration and invasion by increasing focal adhesion kinase and Src activity. In addition, 4-HBA treatment also promoted wound healing and re-epithelialization in anin vivo excision wound animal model. Combination treatment with 4-HBA and platelet-derived growth factor subunit B homodimer showed synergistic effects in promoting wound healing. Taken together, our results demonstrated that treatment with 4-HBA promoted keratinocyte migration and wound healing in mouse skin through the Src/mitogen-activated protein kinase pathway. Therefore, 4-HBA could be a candidate therapeutic agent with the potential to promote acute wound healing.